Effectiveness of Lifestyle Modifications on Blood Sugar Control in Type 2 Diabetes Mellitus Patients : A Systematic Review - Yukmin Rotama Panjaitan; Reski Dwi Indah Sari; Kristian Yanuar Lase (International Medical Journal Corp. Ltd, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a progressive metabolic disorder associated with significant morbidity and healthcare costs. While pharmacological treatments are central, there is growing interest in lifestyle modifications as adjunct or primary interventions. However, the comparative effectiveness of different lifestyle components and the consistency of their glycemic benefits remain unclear. Methods: This systematic review synthesized evidence from 80 studies (including RCTs, etc) identified through systematic screening of abstracts and full texts. Inclusion criteria required adult T2DM populations (≥18 years), lifestyle interventions (diet, exercise, behavioral support, education, or digital tools), and blood glucose outcomes (HbA1c, fasting plasma glucose, postprandial glucose). Data extraction focused on lifestyle intervention details, study population characteristics, glycemic outcomes, secondary cardiometabolic outcomes, and study design. Results: Across the corpus, multicomponent lifestyle interventions produced pooled HbA1c reductions of approximately −0.51% to −0.63% compared to usual care. Exercise interventions, particularly supervised combined aerobic and resistance training, reduced HbA1c by −0.34% to −0.53%, with combined training showing superiority over either modality alone. Dietary interventions (Mediterranean, DASH, low-carbohydrate) achieved HbA1c reductions ranging from −0.39% to −0.82%; however, long-term low-carbohydrate diets (≥12 months) showed non-significant effects (SMD −0.11, p=0.32). Diabetes self-management education (DSME) in group formats reduced HbA1c by −0.44% to −0.87% over 6–24 months, while individual education showed benefit only in those with baseline HbA1c >8%. Digital interventions (mobile apps, SMS) reduced HbA1c by −0.40% to −0.53%, with healthcare professional feedback as a key moderator. Yoga produced consistent improvements (HbA1c MD −0.47%). Intensive lifestyle interventions achieved diabetes remission in 7–12% of participants. Secondary benefits included weight loss, blood pressure reduction, improved lipids, and reduced medication requirements. Discussion: The heterogeneous effect sizes across studies are systematically explained by three interacting mechanisms: baseline glycemic status (individuals with HbA1c ≥8% show twice the benefit), intervention intensity (supervised, high-frequency, and multicomponent programs produce larger effects), and sustainability (benefits attenuate beyond 12 months without ongoing contact). Weight loss is an important mediator but not the sole pathway; direct improvements in skeletal muscle glucose uptake, reduced postprandial carbohydrate load, and enhanced insulin sensitivity contribute independently. Specific recommendations are derived for clinically relevant subgroups. Conclusion: Lifestyle modifications significantly improve blood sugar control in T2DM, with clinically meaningful effects that are comparable to some pharmacological add-on therapies. The greatest benefits occur in patients with higher baseline HbA1c (≥8%) receiving intensive, multicomponent, and supervised interventions. Future clinical practice should prioritize combined diet-plus-exercise programs, group-based DSME with ongoing contact, and targeted digital tools with provider feedback.